Memerankan Disiplin Antropologi Hukum Dalam Penyelesaian Sengketa Agraria - imam koeswahyono (Universitas PGRI Adi Buana Surabaya, 2015)
Approach to study of law especially for dispute resolution concerning agrarian resources has been bound on normative positivistic approach